Edible and Medicinal Pteridophytes of Nepal: A Review - Ojha, Rijan; Devkota, Hari Prasad (Ethnobotany Research and Applications, 2021)
Background: Traditional use of pteridophytes as food and medicine is a common practice around the world. Many ethnic communities hold vast knowledge about the uses of pteridophytes and the documentation of such knowledge and biodiversity of edible and medicinal pteridophytes is important for health care, food security and conservation. Although being one of the biodiversity rich countries, the detailed use of edible and medicinal pteridophytes from Nepal is not well documented and they are one of the underutilized plant resources having vast potential. Thus, the aim of this review is to compile the knowledge about the use of edible and medicinal pteridophytes in Nepal. Methods: Relevant information on traditional uses as medicinal and edible species were collected form published literatures such as research articles on ethnobotanical surveys, books, book chapters and conference proceedings. Results: The literature survey revealed that a total of 26 species of pteridophytes were used as food and 43 species were used as traditional medicines. Among 55 useful species, 14 species were used as both food and traditional medicine. Diplazium esculentum, Diplazium maximum, Dryopteris cochleata and Ophioglossum reticulatum were common edible species and Aleuritopteris albomarginata, Equisetum ramosissimum, Nephrolepis cordifolia and Tectaria coadunata were common medicinal pteridophytes. Most of species are growing in natural habitat and the potential utilization species were sold in the market which has also supported livelihood. Some of these pteridophytes were also used in preparation of ethnic foods such as fermented foods and pickles. Conclusion: Findings from the study suggested that only a few common species of pteridophytes are used as food and traditional medicines Nepal. The knowledge about the traditional uses of pteridophytes and their biodiversity is also affected by socioeconomic changes in communities, lack of sharing of traditional knowledge through generations, improper collection practices and climate change. Very few pteridophytes from Nepal have been studied in detail for their phytoconstituents and biological activities and safety. Future research activities should focus on providing scientific evidence for traditional uses as well as development of proper conservation, cultivation, and product formulation methods in a sustainable manner. Keywords: Conservation, ferns, fern allies, food security, human health